004.6 High prevalence of bacterial vaginosis among adolescent girls attending secondary school in tanzania. (13th September 2015) - Francis, SC; Hansen, C; Irani, J; Andreasen, A; Jespers, V; Nnko, S; Crucitti, T; Changalucha, C; Watson-Jones, D; Buve, A
Abstract : Introduction: Prevalence and incidence of HIV infection and other sexually transmitted infections (STI) are particularly high among adolescent girls in sub-Saharan Africa. One area in need of further research is the role played by the vaginal microbiota in the susceptibility to HIV and other STI in adolescent girls. The aim of this study was to characterise the vaginal microbiota of adolescent girls in Tanzania around the time of their sexual debut. Methods: Girls attending secondary schools in Mwanza City, ages 17 and 18 years old, were invited to join a cross-sectional study. After informed consent/assent, girls were interviewed and nurse-assisted, self-collected swabs were obtained for STI and BV testing. BV was considered as a binary outcome: Nugent scores 7–10 were considered BV positive. Factors associated with prevalent BV were analysed using multivariable logistic regression. Results: Of the 403 girls who enrolled in the study, 176 (44%) reported having had sexual intercourse and 8 (2%) reported receiving cunnilungus. Ninety-five (25%) girls had BV, 9 (2%) were infected with Chlamydia trachomatis, 8 (2%) had Neisseria gonorrhoea, 18 (5%) had Trichomonas vaginalis, 85 (21%) had Human papilloma virus and 6 (2%) Mycoplasma genitalium . Six (2%) girls were infected with HSV-2. Among girls who were sexually naïve, 19% had BV compared to 32% in sexually active girls. BV was independently associated with sexual debut (aOR = 2.11; 95% CI: 1.32, 3.39); oral sex (aOR = 7.94; 95% 1.53, 40.3); >1 sex partner (aOR = 2.55; 95% CI: 1.21, 5.39); and HPV (aOR = 1.73; 95% CI: 1.02, 2.94). Conclusion: In this study among girls attending secondary school in Mwanza, Tanzania, sexual debut was associated with BV; however, 19% of girls who were sexually naïve had BV. This suggests that sexual intercourse may not be a prerequisite for BV. Oral sex was also associated with BV although the reported prevalence of this sexual behaviour was low. Disclosure of interest statement: The authors do not have a conflict of interest. No pharmaceutical grants were received in the development of this study.